Answer:
B.
Explanation:
To get the inverse of the function defined by the table given, all you need to do is to interchange the coordinate pairs.
That is, the coordinates pair on a table that defines a function is usually given as (x, y). The inverse of the function would be (y, x).
The following are the coordinate pairs given and the inverse of the function represented:
(x, y) => inverse = (y, x)
(7, 21) => inverse = (21, 7)
(10, 30) => inverse = (30, 10)
(13, 39) => inverse = (39, 13)
(16, 48) => inverse = (48, 16)
The table that represents the inverse of the function given in the question is option B